The durability performance of rubberized-ultra high performance concrete exposed in magnesium sulphate and hydrochloric acid - Muhamad Hariz, Ibrahim (2018)
Tyre rubber waste is one of significant waste that should be more concerned due to the increasing in the number of vehicles. Moreover, the increasing volume of tyre rubber waste will give bad impact to environment. Previously, utilization of tyre rubber waste on properties of concrete and applications of rubberized concrete had been explored. In this study, the application of rubberized concrete in UHPC. Ultra-High-performance concrete (UHPC) is a construction material with excellent mechanical properties and good durability as compared to conventional concrete. It can contribute to the longer life and economic efficiency of structures. UHPC is high strength material created by using coarse, fine and ultrafine aggregates, very low amounts of water, silica fume and high amounts of cement. Besides, UHPC has some limit Tyre rubber waste is one of significant waste that should be more concerned due to the increasing in the number of vehicles. Moreover, the increasing volume of tyre rubber waste will give bad impact to environment. Previously, utilization of tyre rubber waste on properties of concrete and applications of rubberized concrete had been explored. In this study, the application of rubberized concrete in UHPC. Ultra-High-performance concrete (UHPC) is a construction material with excellent mechanical properties and good durability as compared to conventional concrete. It can contribute to the longer life and economic efficiency of structures. UHPC is high strength material created by using coarse, fine and ultrafine aggregates, very low amounts of water, silica fume and high amounts of cement. Besides, UHPC has some limitations in terms of cost and availability of raw constituent materials. The UHPC is required the large amount of sand, aggregates and cement. Therefore, it is has led to depletion of natural sources, so it is give idea to replace 5% crumb tyre as aggregates from total weight aggregates.